Analisis Molekuler dan Keragaan Agronomis Galur-galur Padi BC1F1 Persilangan Code x qTSN4 dan Code x qDTH8 (Molecular Analysis and Agronomic Performance of BC1F1 Crosses Code x qTSN4 and Code x qDTH8) - Tasliah Tasliah; Ma'sumah Ma'sumah; Kurniawan R. Trijatmiko; Joko Prasetiyono (Jurnal AgroBiogen, 2015)
Breeding based on molecular marker has become a routine activity in the current rice research. The development of an earlymaturity of rice variety with high yield is needed to increase national rice production. This study aimed to determine the patternof alleles for loci controlling total spikelet number and number of days to heading, as well as agronomic performances of theBC1F1 Code x qTSN4 and Code x qDTH8 populations. The study was conducted at the Indonesian Center for Biotechnology andGenetic Resources Research and Development from January to August 2014. The plant materials used were Code (a nationalvariety with bacterial blight resistance gene [Xa7]), IR64-Nils-qTSN4[YP9] (qTSN4 that contains a locus controlling the number ofspikelet), IR64-Nils-qDTH8[YP1] (qDTH8 that contains a locus controlling the number of days to heading), BC1F1 Code x qTSN4,and BC1F1 Code x qDTH8. A total of 250 BC1F1 plants of each crosses were selected using molecular markers of RM20582 for Xa7gene, RM17483 and RM6909 for QTL position of qTSN4, RM5556 and RM6838 for QTL position of qDTH8. Based on molecularanalysis, there were 63 BC1F1-qTSN4 lines and 65 BC1F1-qDTH8 lines showing heterozygote alleles for qTSN4 or qDTH8 loci andwere homozygote for Xa7 locus (HHA pattern). Five plants from each locus target were backcrossed to the recurrent parent,Code, to obtain BC2F1 seeds. The remaining BC1F1 plants were self-pollinated to obtain BC1F2 seeds. Observations on someagronomic characters demontrated that the BC1F1 plants showed higher yield potential than Code and the flowering time of theBC1F1 progenis were also earlier than Code. These results indicated that the yield potential of Code could be improved byintrogression of qTSN4 and qDTH8 loci into the Code genome.